Effects of tool offset and reversed metal flow on mechanical properties of dissimilar friction stir welded T-lap joints between AA7075 and AA5083 - Hao Dinh DUONG (The Japan Society of Mechanical Engineers, 2020)
The effects of tool offset and the reversed metal flow induced by a double-pass friction stir welding (FSW) on the welding interface characteristics were investigated in a dissimilar thickness T-lap joint between 7075-T651 and 5083-H116 aluminum alloys. The performance of the joint was evaluated by the skin and stringer tensile tests. The experimental results showed that the bonding interface could be improved by applying double-pass welding which the tool was offsetted toward advancing side. An employment of the double-pass welding significantly improved the strength so that the joint efficiency reached about 90% in comparison with the 5083 base metal strength while the tensile strength of the joint produced by the single-pass welding was quite low. The kissing bond defects were found to be the main culprit in the tensile behavior of the T-lap joint. The reversed metal flow and the gap distance between pin and die played a key role in the formation of the welding interface.